RANCANG BANGUN WEB ECOMMERCE DENGAN DASHBOARD SYSTEM AKSESORIS DAN MAINAN ANAK PADA UD SINAR GEMILANG SURABAYA - Domingos Sinorio de Araujo; Eni Farida; Indah Dwi Mumpuni (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2024)
The scope marketing of UD Sinar Gemilang is still based in the Surabaya and is still face to face marketing (face-to-face with the customers). Moreover, if existing the remaining stock of products distributed then UD Sinar Gemilang can’t sell them in retail.This Ecommerce can help UD Sinar Gemilang sell the remaining stock and also expand the marketing network. This ecommerce was designed using object-oriented methods, namely the making Use Case, Activity Diagram, Sequence Diagram and Class Diagram for designing and documenting software systems based Data flow.This ecommerce has two pages, admin pages and user pages. Admin login divided into two levels: admin and super admin. Admin can only access content that is transactional, while for the control fully assigned to the owner as Super admin. Admin page load master data, such as product data, user data, customer data, transaction data and reports. User pages can be accessible by anyone without limitation of the right access, but users are required to make a reservation for the first login, the user page contains product data and transaction.